PENDUGAAN CADANGAN KARBON DI ATAS PERMUKAAN TANAH PADA KAWASAN TATA HIJAU PENYAMBUT TAMAN HUTAN RAYA (TAHURA) SULTAN SYARIF HASYIM PROVINSI RIAU - Saputra, Donald; Sulaeman, Rudianda; M. Mardhiansyah, M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Forests are natural resource that provides great benefits for human welfare, both tangiblele and intangible benefits. The tangible benefits such as timber and non-timber forest products. Moreover, the intangible benefits such as recreational areas, protection and regulatory systems, micro climate regulators, erosion preventer and as carbon storage. Therefore, this research is aimedto determine the potential of carbon stocks above the surface of the soil one of the areas in Taman Hutan Raya (Tahura) Sultan Syarif Hasyim called Kawasan Tata Hijau Penyambut, Riau Province. Approximately 65.05 Ha, with a sampling intensity value of 3%. Plot determination and data retrieval has done by random sampling which research sampling method giving equal opportunity to be taken in every element of population or region. The collected data includes initial weight value, sample weight and dry weight at litter, seedling and under plant level. At the stake, pole and tree level, the collected data are local names, scientific names and diameter values of stands. The data was processed to calculate the value of the content of the biomass by summing the biomass at the level of stakes, poles and trees by using the equation of allometrik and biomass at a rate of litter, seedlings and lower plants using the formula from Indonesian National Standard. Based on the research that has been done, the potential of carbon content in Kawasan Tata Hijau was 136,28 ton/ha or 8.865 ton if extrapolated to the total area of the whole area.Keywords: Forest, Taman Hutan Raya, Biomass, Carbon